EFFECT OF FORCED INSPIRATORY AND EXPIRATORY MANUEVER IN PATIENTS WITH CERVICAL SPONDYLOSIS - JESSE MAGH; R.ARUNACHALAM (International Journal of Pharma and Bio Sciences, 2016)
Neck pain is a common problem that one encounter at some point in their lives. Progressive neck pain is a key indication of cervical spondylosis. Some of the muscles which help in improving the stability of the cervical spine also serve as an accessory muscle for force expiration and inspiration. This additional function of neck stabilizing muscles is utilized in strengthening our program. Thirty subjects from OPD (Out Patient Department) of Saveetha physiotherapy Chennai were randomly allocated to Group A & B. Group A receives conventional physiotherapy with Maneuver technique. Group B received conventional physiotherapy only. Pain, cervical range of motion and cervical muscle power was assessed using visual analog scale, Range of Motion of cervical rotation and isometric hold time. Statistical analysis showed significant difference (p<0.001) between pre and post test values of Group A and B for the outcome measure of VAS. (p<0.001) to isometric hold time and (p<.0.005) for cervical range of motion.